The Use of English Movie Assisted Role Playing Technique toward Students’ Vocabulary Mastery - Yashori Revola (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2019)
The result of this research showed that the experimental group got better than the control group. In experimental group the highest score gained by the students was 90 and the lowest score was 60. While in control group the highest score was 75 and the lowest score was 35. The students of two groups had different achievement vocabulary after treatment. The students‘ vocabulary achievement in experimental group was increasing and the score was high, but the control group the students’ vocabulary achievement was still low. It meant that there was a significant difference on students’ vocabulary achieved by students who have been taught using English movie assisted role-playing technique. In line with the result: the researcher suggested that English movie with role-playing technique to be used as an aid to teach students vocabulary mastery. The purpose was to create a situation that made students are interested and more active for learning English.